Sphagnum-associated chrysophytes from the “Dermansko-Ostrozsky” National Nature Park (Ukraine) - Dmitry Kapustin; Maxim Kulikovskiy (Mires and Peat, 2023)
Eight chrysophyte species and eight chrysophycean stomatocyst morphotypes associated with Sphagnum were recorded from a peatland (fen) within the “Dermansko-Ostrozsky” National Nature Park. The morphology of siliceous scales and stomatocysts was studied using scanning electron microscopy (SEM). Poterioochromonas malhamensis was recorded for the first time in Ukraine, and one of the chrysophycean stomatocyst morphotypes described was new to science.